2011
DOI: 10.1007/s11595-011-0334-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural features and properties of high-hardness and heat-resistant dispersion strengthened copper by reaction milling

Abstract: The oxide dispersion strengthened copper alloys are attractive due to their excellent combination of thermal and electrical conductivities, high-temperature strength and microstructure stability. To date, the state-of-art to fabrication of them was the internal oxidation (IO) process. In this paper, alumina dispersion strengthened copper (ADSC) powders of nominal composition of Cu-2.5 vol%Al 2 O 3 were produced by reaction milling (RM) process which was an in-situ gas-solid reaction process. The bulk ADSC allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The presence of these defective structure decreases the diffusion distances and increases the diffusivity of oxygen absorbed on the particle surface into the copper matrix at low temperature as interstitial and substitutional atoms. Besides, the slight raise in temperature during milling aids the oxygen diffusion, and consequently, selective reaction takes place among the copper and oxygen atoms [13]. Unfortunately the oxygen content measured by LECO is affected by the amount of oxygen present on the powder surface, so actual oxygen dissolved in the copper matrix is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these defective structure decreases the diffusion distances and increases the diffusivity of oxygen absorbed on the particle surface into the copper matrix at low temperature as interstitial and substitutional atoms. Besides, the slight raise in temperature during milling aids the oxygen diffusion, and consequently, selective reaction takes place among the copper and oxygen atoms [13]. Unfortunately the oxygen content measured by LECO is affected by the amount of oxygen present on the powder surface, so actual oxygen dissolved in the copper matrix is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the reaction rate of oxidation is enhanced and dynamically extended during the milling as a result of mixing processes and microstructural refinement [10]. Therefore the presence of oxygen in the MM system could affect severely the chemical, physical and mechanical properties of the final product [9,[11][12][13][14]. Parameters such as milling time, process control agent or the choice of a continuous or interrupted cycle determine the characteristics of the milled powders and the level of oxygen absorbed [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The peaks of α-Al2O3 have peak width (FWHM) in the order of 0.1° which are considerably sharper than those of η-Al2O3 with FWHM in the order of 1°, indicating significantly larger particle size of α-Al2O3. Both α-Al2O3 and η-Al2O3 have been observed in internal oxidation ODS copper [9], [13], [16], [17], [20]. In principle, the particle sizes can be analyzed by XRD peak width by using Scherrer equation.…”
Section: Resultsmentioning
confidence: 99%
“…Due to these favourable atrributes, powder metallurgy copper and copper alloy products are widely used in automotive, appliance, electronics, communication and other areas, and thus play an important role in industrial production [7][8][9][10][11][12] . Compared with conventional sintering methods, the spark plasma sintering (SPS) can save energy and time, improve the equipment efficiency.…”
Section: Introductionmentioning
confidence: 99%